INSPIRE: INvestigating Stellar Population In RElics VIII. Emission lines and UV colours in ultracompact massive galaxies - Spiniello, Chiara; Radovich, Mario; Ferre-Mateu, Anna; De Propris, Roberto; Arnaboldi, Magda; La Barbera, Francesco; Hartke, Johanna; D'Ago, Giuseppe; Tortora, Crescenzo; Bevacqua, Davide; Maksymowicz-Maciata, Michalina; Mills, John; et al. (OXFORD UNIV PRESS, 2025)
We report the discovery of emission lines in the optical spectra of ultracompact massive galaxies (UCMGs) from INSPIRE including relics, which are the oldest galaxies in the Universe. Emission-lines diagnostic diagrams suggest that all these UCMGs, independently of their star formation histories, are 'retired galaxies'. They are inconsistent with being star-forming but lie in the same region of shock-driven emissions or photoionization models, incorporating the contribution from post-asymptotic giant branch (pAGB) stars. Furthermore, all but one INSPIRE objects have a high [O ii]/Hα ratio, resembling what has been reported for normal-size red and dead galaxies. The remaining object (J1142+0012) is the only one to show clear evidence for strong active galactic nucleus activity from its spectrum. We also provide near-UV (far-UV) fluxes for 20 (5) INSPIRE objects that match in GALEX. Their NUV-r colours are consistent with those of galaxies lying in the UV green valley, but also with the presence of recently (≤ 0.5 Gyr) formed stars at the sub-per cent fraction level. This central recent star formation could have been ignited by gas that was originally ejected during the pAGB phases and then re-compressed and brought to the core by the ram-pressure stripping of Planetary Nebula envelopes. Once in the centre, it can be shocked and re-emit spectral lines.